Avaliação dos Teores de Elementos em Amostras de Água e Sedimentos da Bacia Hidrográfica Rio Reis Magos - ES: Em Busca de Indícios de Impactos Antrópicos - Barbieri, Eldis Maria Sartori (2022)
Anthropogenic activities can cause important environmental impacts, since the contribution of trace elements in ecosystems affect geochemical cycles and present toxicity to living beings. When these elements are carried to aquatic systems, they are distributed between water and sediments, and most of them accumulate in sediments due to adsorption, hydrolysis and co-capacity processes, therefore, they are potential sources of contamination, as they can re-available them in the water body. Therefore, research with sediments is fundamental to verify the anthropic contribution in the structure of these ecosystems, having as polluting sources direct discharges of effluents and solid residues, agricultural defensives, fertilizers, atmospheric deposition and sediment transport. With the water crisis, the Government of Espírito Santo (Brazil) started to use, in 2017, the Reis Magos River for public supply, however, this hydrographic basin has been suffering important environmental impacts, however, despite its importance, there is still no data provided published regarding its environmental quality. Thus, the present work aimed to quantify the requirements of As, Cd, Co, Cr, Cu, Fe, Mn, Hg, Ni, Pb, Sb e Zn, organic matter and carbonate content, pH, granulometric and crystallographic study in sediment. For water samples determination of pH, temperature (T), electrical conductivity, turbidity, oxydation reduction potential (ORP), dissolved oxygen (DO), total dissolved solids (TDS) and salinity of the Basin of the River Reis Magos. To assess the probability of adverse effects to biota, the values by the Canadian Council of Ministries of Environment that recommend threshold effect level (TEL) and probable effects level (PEL) concentration levels were adopted. In order to measure the degree of anthropogenic contribution, enrichment factors (EF), contamination (FC) and the geoaccumulation index (Igeo), pollution load index (PLI) and potential ecological risk (EF) were determined. The correlation between the variables made by principal component analysis (PCA), showing a direct relationship between the degree of source and proximity to the urban center, alkaline mineralogical characteristics cause an increase in pH and the higher the content of fines and organic matter, the greater the concentration of trace elements. For the water samples the concentrations of As, Cr, Cu and Fe presented more alarming values, above those allowed by law (10, 50, 9 and 300 µL L-1, respectively), mainly in the Reis Magos River. According to the general assessment, the sediments have mild to severe degrees of contamination, with a range of EF 5.67 - 384.02, suggesting a possible anthropic contribution.